Co-Financing Agreements and Reciprocity: When 'No Deal' is a Good Deal - Dooseok Jang; Amrish Patel; Martin Dufwenberg (Center for Economic Studies and ifo Institute (CESifo), 2016)
Institutions for co-financing agreements often exist to encourage public good investment. Can such frameworks deliver maximal investment when agents are motivated by reciprocity? We demonstrate that indeed they can, but not in the way one might expect. If maximal investment is impossible in the absence of the institution and public good returns are high, then an agreement signed by all parties cannot lead to full investment. However, if all parties reject the co-financing agreement, then an informal deal to invest can lead to full investment. Agreement institutions may thus do more than just facilitate the signing of formal agreements; they may play a critical role in igniting informal cooperation underpinned by reciprocity.
Keywords: C72; D03; F53; H41; 330; co-financing agreements; informal agreements; public goods; reciprocity